Condomínios horizontais fechados (CHF): o modelo Alphaville e o ensino de Geografia - Rodrigues, Jailton Aparecido (2013)
The purpose of this research was the Barueri-Santana de Parnaíba (São Paulo State) Alphaville, the first Closed Horizontal Condominium (CHF, in Portuguese) in Brazil. Alphaville was the theme for studying concepts related to spatial segregation to better understand the urban restructuring. This research also is addressed to school teachers and students and teachers of undergraduate courses in Geography to contribute to debate on teaching of discipline. This work was divided into two sections: the first was a review of theoretical literature on the subject; the second involved practical activities for elementary school students on the theme of CHF as an aid in understanding some fundamental concepts of Geography and concepts related to socio-spatial inequality, closely related to the subject